Infant Appetitive Phenotypes: A Group-Based Multi-Trajectory Analysis - Russell, Catherine G.; Appleton, Jessica; Burnett, Alissa J.; Rossiter, Chris; Fowler, Cathrine; Denney-Wilson, Elizabeth; Jansen, Elena (Frontiers in Nutrition, 2021)
Background: Examining appetitive traits with person-centered analytical approaches can advance understanding of appetitive phenotype trajectories across infancy, their origins and influences upon them. The objective of the present study was to empirically describe appetitive phenotype trajectories in infancy and examine associations with infant and parent factors. Materials and Methods: In this longitudinal cohort study of Australian infants, parents completed three online surveys approximately three months apart, beginning when the infant was < 6 months. Appetitive traits were assessed with the Baby Eating Behaviour Questionnaire (BEBQ), and parent feeding practices with the Feeding Practices and Structure Questionnaire (FPSQ) infant and toddler version. Parent demographics and cognitions were also collected. Infant weight and length were transcribed from health records and converted to a Body Mass Index (BMI) z-score. Group-based trajectory modelling identified appetitive phenotype trajectories using the BEBQ. Multilevel modelling examined change in feeding practices and child BMI z-score over time by appetitive phenotype trajectories. Results: At time 1, 380 participants completed the survey (mean infant age 98 days), 178 at time 2 (mean infant age 198 days), and 154 at time 3 (mean infant age 303 days). Three multi-trajectory appetitive phenotype groups were identified, labelled as: (Phenotype 1) food avoidant trending towards low food approach (21.32% of infants), (Phenotype 2) persistently balanced (50.53% of infants) and (Phenotype 3) high and continuing food approach (28.16% of infants). Formula feeding was more common in Phenotype 1 (p=0.016). Parents of infants in Phenotype 1 were more likely to rate them as being more difficult than average, compared to infants with phenotypes 2 or 3. Phenotype 2 had the greatest increase in persuasive feeding over time (0.30; 95% CI [0.12, -0.47]). Conclusions: Distinct multi-trajectory appetitive phenotype groups emerge early in infancy. These trajectories appear to have origins in both infant and parent characteristics as well as parent behaviors and cognitions. The multi-trajectory appetitive phenotype groups suggest that for some infants difficulties in self-regulating appetite emerge early in life. Investigation of infant multi-trajectory appetitive phenotype groups that utilize a range of measures, examine relationships to covariates and outcomes, and extend from infancy into childhood are needed.